2020
DOI: 10.3390/w12092339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Catchment Discretization and Imputed Radiation on Model Response: A Case Study from Central Himalayan Catchment

Abstract: Distributed and semi-distributed hydrological modeling approaches commonly involve the discretization of a catchment into several modeling elements. Although some modeling studies were conducted using triangulated irregular networks (TINs) previously, little attention has been given to assess the impact of TINs as compared to the standard catchment discretization techniques. Here, we examine how different catchment discretization approaches and radiation forcings influence hydrological simulation results. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 68 publications
0
4
1
Order By: Relevance
“…The efficiency parameters for this subcatchment are less satisfying than for 8 and 13, notifying us that there is actually no reason for more cells, as source data might be a greater issue. However, for CID-10 we found that grid-based solution perform better than TIN-based, which seems to be contradictory to our study (Bhattarai et al, 2020b) with CID-10, so additional investigations needed to understand such difference.…”
Section: Recent Applicationcontrasting
confidence: 99%
See 4 more Smart Citations
“…The efficiency parameters for this subcatchment are less satisfying than for 8 and 13, notifying us that there is actually no reason for more cells, as source data might be a greater issue. However, for CID-10 we found that grid-based solution perform better than TIN-based, which seems to be contradictory to our study (Bhattarai et al, 2020b) with CID-10, so additional investigations needed to understand such difference.…”
Section: Recent Applicationcontrasting
confidence: 99%
“…This study is our first step in assessing benefits for the practitioners in the power production industry, and the results are promising. Further study by Bhattarai et al (2020b) gives more light on the usage of TIN-mesh for hydrological simulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations